Multiple Sites Ultrasonography of Peripheral Nerves in Differentiating Charcot–Marie–Tooth Type 1A from Chronic Inflammatory Demyelinating Polyradiculoneuropathy - Niu, Jingwen; Cui, Liying; Liu, Mingsheng (Frontiers in Neurology, 2017)
Introduction: Multiple sites measurement of cross sectional areas (CSA) by ultrasound was performed to differentiate Charcot-Marie-Tooth type 1A (CMT1A) and chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Methods: Nine patients with CMT1A, 28 patients with CIDP, and 14 healthy controls (HC) were recruited prospectively. Consecutive ultrasonography scanning was performed from wrist to axilla on median and ulnar nerves. CSAs were measured at 10 predetermined sites of each nerve. Results: CMT1A had significantly larger CSAs at all sites of median and ulnar nerves (P<0.01). In CMT1A, CSAs increased gradually and homogeneously from distal to proximal along the nerve, except potential entrapment sites. CIDP displayed three different morphological patterns, including mild enlargement in 15 patients, prominent segmental enlargement in 12, and slight enlargement in one, among which different treatment responses were observed. All patients with mild nerve enlargement treated with intravenous immunoglobulin (IVIG) were responsive (7/7), while less than half of those with prominent segmental enlargement (3/7) were responsive (p<0.01). Discussion: Consecutive scan along the nerve and multiple sites measurement by ultrasound could supply more detailed morphological feature of the nerve and help to differentiate CMT1A from CIDP. □